Development and Usability Evaluation of an Elective Course Recommendation System Based on Student Interests and Abilities - Mochammad Yussack Saputra; Sukirman Sukirman; Dias Aziz Pramudita (Papanda Publisher, 2026)
Elective course selection is a critical academic decision in higher education; however, students frequently rely on peer conformity rather than systematic self-assessment, resulting in competency–course mismatches and suboptimal academic outcomes. Existing decision support systems have addressed this problem algorithmically, yet few have integrated psychological interest profiling within a usability-evaluated web-based platform. This study employed a Research and Development (R&D) design with the waterfall development model across four phases: needs analysis, system design, implementation, and testing. A web-based elective course recommendation system — integrating a psychological interest assessment as the recommendation engine — was developed using PHP, MySQL, Laravel, and Bootstrap. Usability was evaluated by 10 purposively selected students using the System Usability Scale (SUS), and data validity was assessed through Pearson correlation analysis. The system achieved a mean SUS score of 81.3, classifying it within the